Monetary Policy and Productivity Nexus for Africa’s Oil Exporting Countries: An Econometric Analysis: Array - Olamide, Ebenezer; Ogujiuba, Kanayo; Maredza , Andrew; Adeleke , Omolade (Acta Universitatis Danubius. Œconomica, 2022)
Objectives: The danger of export dependent economies is exposure to external shocks, that weakens the domestic economy, which is evident in Africa’s oil producing countries. The fortunes from increased oil revenue by these countries, have been sabotaged through the same shocks in oil prices, leading to inconsistencies in monetary policy. This article examined responses of monetary policy in Africa’s oil producing countries to oil prices and by extension its effect on manufacturing products. Prior Work: Previous research had mixed results on the relationship with inflation and its effect on growth. Thus, it wasn’t clear the effect on manufacturing industries’ output. Approach: The technique adopted for this study is the panel data error correction approach. The technique uses structure dynamics rather than residual dynamics and does not impose restriction of common factors like the residual dynamics approach. The procedure has three stages, namely, stationarity testing, error-correction-based panel cointegration test and the estimation of both the long-run and the short-run equations. Results: The results show a weak long–run relationship between individual monetary policy variables and manufacturing sector growth. In both the static and dynamic panel models, all monetary policy variables demonstrate more significant impact in the short run than in the long run. Implications: The undervaluation of a currency has a significant and positive relationship with manufacturing growth rate in the AOECs. This suggests that a fall in the value of a currency, has the tendency of boosting domestic output and consequently promotes the growth of the real sector Value: Our results support the inverse relationship between manufacturing sector growth rate and net domestic credit. The finding supports the growing literature on the undervaluation of currencies and growth in most developing countries. Our research has shown that a combination of monetary variables will have a significant impact on the growth of the manufacturing sector in the AOECs.